Space-time symmetry from the world-sheet - Kiarash Naderi (Journal of High Energy Physics)
Abstract The tensionless string on AdS3 is a laboratory to study different aspects of the AdS/CFT correspondence. A particular question addressed in this paper is how the space-time symmetry algebra is encoded on the world-sheet. A natural prescription for calculating the space-time OPEs from the world-sheet is presented in the hybrid formalism. An argument showing that the OPEs are correctly reproduced from the world-sheet is provided, together with a few explicit calculations as consistency checks.